Protocol of the evolution study: A prospective, multicenter, observational study evaluating the effect and health economics of endovascular treatment in patients with moderate and severe calcification of femoropopliteal artery - Pan, Jun; Guo, Lianrui; Fang, Xin; Feng, Zibo; Li, Qiang; He, Chunshui; Sang, Hongfei; Shi, Weihao; Shi, Zhenyu; Wang, Bing; Qiu, Chenyang; Wu, Ziheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Peripheral artery disease with calcification is extremely prevalent in the elderly. Due to the calcification, it requires a different clinical approach than the more common arteriosclerosis obliterans of the lower extremity. The introduction of novel technologies such as the drug-coated balloon, directional atherectomy, supera and drug-eluting stent has improved the prognosis of these patients. This study will contribute to the development of higher-quality evidence-based medicine for clinical treatment by assessing the quality of life (QOL), clinical treatment effect, and health economics of patients with calcification. Method and analysis: The Evolution study is designed as a prospective, multicenter, observational, real-world study. From January 2021 to December 2022, 600 patients with moderate to severe femoropopliteal artery calcification will be recruited from ten locations in China. After discharge, information on demographics, disease history, procedure details, imaging findings, and follow-up will be collected. Patients will undergo follow-up at 1, 6, 12, 18 and 24 months after operation. Technical success rate, vascular quality of life questionnaire, primary patency rate of the target lesion, clinically driven target lesion revascularization rate (CD-TLR), and health economics evaluation are all included as outcome measures. Conclusions: The Evolution study helps to investigate the clinical and financial results of various endovascular therapy modalities for patients with moderate and severe femoropopliteal artery calcification. These actual facts may help to harmonize therapy recommendations for peripheral artery disease. Ethics and dissemination: The study protocol was registered at www.clinicaltrials.gov (registration number: NCT04716361). The study protocol has been approved by the Institutional review board and Human Research Ethics Committee of the first affiliated hospital of Zhejiang university, and by the ethics committees of all participating centres. The results of this investigation will be published in a peer-reviewed journal.